2020
DOI: 10.1042/bcj20190462
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of adipose surface epitopes

Abstract: Adipose tissue is a central regulator of metabolism and an important pharmacological target to treat the metabolic consequences of obesity, such as insulin resistance and dyslipidemia. Among the various cellular compartments, the adipocyte cell surface is especially appealing as a drug target as it contains various proteins that when activated or inhibited promote adipocyte health, change its endocrine function and eventually maintain or restore whole-body insulin sensitivity. In addition, cell surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 403 publications
(512 reference statements)
0
7
0
Order By: Relevance
“…Clusters 0, 1 and 2 were assigned with a number of distinct pathways, whereas cluster 3 shared most of its enriched pathways except “Wnt signaling” with other clusters. Cluster 0 associated with peroxisome proliferator-activated receptor (PPAR) and Apelin signaling, both important for terminal brown adipocyte differentiation ( 29 , 30 ), whereas clusters 1–3 showed an enrichment in pathways, such as WNT, TNF, relaxin, and TGFβ signaling that are generally associated with the inhibition of adipogenesis ( 31 , 32 , 33 ). Interestingly, cluster 3 shared most pathways with other clusters, regardless of their distance in the louvain plots.…”
Section: Resultsmentioning
confidence: 99%
“…Clusters 0, 1 and 2 were assigned with a number of distinct pathways, whereas cluster 3 shared most of its enriched pathways except “Wnt signaling” with other clusters. Cluster 0 associated with peroxisome proliferator-activated receptor (PPAR) and Apelin signaling, both important for terminal brown adipocyte differentiation ( 29 , 30 ), whereas clusters 1–3 showed an enrichment in pathways, such as WNT, TNF, relaxin, and TGFβ signaling that are generally associated with the inhibition of adipogenesis ( 31 , 32 , 33 ). Interestingly, cluster 3 shared most pathways with other clusters, regardless of their distance in the louvain plots.…”
Section: Resultsmentioning
confidence: 99%
“…However, other recent studies revealed non-perivascular adipose precursor populations [ 45 , 127 ]. Thus, it is not surprising that this diversity has led to the characterization of various cell types believed to be WAT progenitors (reviewed in [ 128 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, Rodeheffer et al identified and Berry et al characterized a subpopulation of early adipocyte progenitors defined as CD24 + CD29 + CD34 + Sca-1 (Ly6A) + in mouse WAT [ 31 , 129 ]. Since then, many studies have found distinct adipocyte progenitor cells with various cell surface proteins expressed in WAT [ 128 ] and, recently, single-cell RNA sequencing (scRNAseq) technology was used to find new gene markers able to better define the cellular subpopulation involved in adipogenesis (reviewed in [ 130 , 131 ]). This new way to search for new markers led David Merrick et al [ 45 ] to identify distinct types of progenitor cells in murine subcutaneous adipose tissue, which were subdivided into three hierarchical groups based on their gene expression patterns (reviewed in [ 132 , 133 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to indirect proteomic techniques, phage display allows probing of proteins in their native context during biopanning, thus increasing the clinical relevance of the identified targeting agents. 50 Additionally, in vivo screening ensures identifying targeting agents with high selectivity as subtractions for all other tissues are carried out while enrichment occurs in the target tissue. 19 By comparing the in vivo screens against CP, benign pancreas, and pancreatic cancer using our database, we were able to ensure peptide selectivity to the diseased pancreas by not choosing peptides in any condition but CP.…”
Section: Discussionmentioning
confidence: 99%